Penggembangan LKPD Berbasis Scaffolding Pada Materi Gelombang (Jurnal Luminous: Riset Ilmiah Pendidikan Fisika, 2026)
This study aims to develop and evaluate the feasibility of a scaffolding-based student worksheet for the topic of waves on a string in senior high school physics learning. This research employed a Research and Development (R&D) method using an adapted ADDIE model, limited to the analysis, design, development, and formative evaluation stages through expert validation. The product was designed based on the need to support students in understanding wave concepts gradually through guided questions, structured learning activities, simulations, and conceptual reflection. Validation was conducted by a material expert and a learning expert. The validation results showed that the worksheet obtained a feasibility score of 80% from the material expert, categorized as feasible, and 88% from the learning expert, categorized as highly feasible. Therefore, the scaffolding-based worksheet for waves on a string is considered feasible as an alternative teaching material in physics learning. The product has the potential to support more guided conceptual learning, although further research is needed to examine its effectiveness in improving students conceptual understanding